Analisis Efisiensi dan Efektifitas Anggaran Belanja Langsung - Studi pada SKPD di Pemerintah Kota Banda Aceh - Fahlevi, Heru; Ananta, Muhammad Reza (Badan Penerbitan Jurnal (BPJ) FIA-UB, 2015)
The objective of this study is to analyze the efficiency and affectivity of direct spending budgeting of Satuan Kerja Perangkat Daerah (SKPD) of Banda Aceh city to identify factors that determine their efficiency and affectivity. It is a descriptive and explorative study that used both primary and secondary data. The data was collected from Laporan Realisasi Anggaran (LRA) of the studied SKPD between 2009 and 2013. Following that, questionnaires that identified factors that affect the efficiency and affectivity of direct spending budgeting were distributed to 76 respondents who play an important role in budgeting process in their SKPD. This study found that the studied SKPD have a relatively high efficiency and effectiveness, but these figures were varied across SKPD and period of observation. In addition, this study also uncovered that planning issues were the most frequent problems that causes low efficiency and effectiveness of direct spending budgeting in the studied SKPD.